A STUDY OF SOME PRODUCTION CHARACTERISTICS OF DUPSKA PRAMENKA LAMBS WITH THE AIM OF GENETIC CHARACTERIZATION OF THE BREED (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Characterization of animal genetic resources includes all activities related to morphometric, production and genetic characterization. The aim of these work was production characterization of Dupska pramenka, as a valuable genetic resource of Bosnia and Herzegovina. In these paper, parameters of birth weight and development of lambs up to the age of 180 days were monitored. The lambs were raised in extensive feeding conditions. Birth weight was measured for a total of 116 lambs, 47 female and 69 male. The average birth weight of lambs is 3.81 kg, females 3.78 and males 3.83. The weight of the lambs was also recorded at the age of 30, 90 and 180 days old. A total of 30 lambs were monitored, 15 female and 15 male. The average weight of lambs was 10.43 kg (30 days), 20.95 kg (90 days) and 32.75 kg (180 days). Average daily gain of lambs was 221.00 g (0-30 days), 175.67 g (30-90 days) and 130.33 g (90-180 days). The total gain of lambs was 6.62 kg (0-30 days), 10.51 kg (30-90 days) and 11.70 kg (90-180 days). The results showed that there is a statistically significant correlation between some analyzed parameters.